2010
DOI: 10.1261/rna.1883810
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of the RNA kink turn structural motif

Abstract: The kink turn (K-turn) is an RNA structural motif found in many biologically significant RNAs. While most examples of the K-turn have a similar fold, the crystal structure of the Azoarcus group I intron revealed a novel RNA conformation, a reverse kink turn bent in the direction opposite that of a consensus K-turn. The reverse K-turn is bent toward the major grooves rather than the minor grooves of the flanking helices, yet the sequence differs from the K-turn consensus by only a single nucleotide. Here we dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…The C-stems and NC-stems of these K-turns are closed by C-G and sheared tandem G-A base pairs, respectively, and are separated by three- or four-nucleotide bulges (Figure 1C). This nucleotide sequence combination enables the formation of a significant bend (~120°) in the helix axis that is stabilized by protein-RNA or RNA-RNA contacts often distal to the turn itself 23. In isolation, the K-turn sequence motif has been observed to exist as a dynamic population of conformations 33 or to preferentially adopt an extended conformation 47.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The C-stems and NC-stems of these K-turns are closed by C-G and sheared tandem G-A base pairs, respectively, and are separated by three- or four-nucleotide bulges (Figure 1C). This nucleotide sequence combination enables the formation of a significant bend (~120°) in the helix axis that is stabilized by protein-RNA or RNA-RNA contacts often distal to the turn itself 23. In isolation, the K-turn sequence motif has been observed to exist as a dynamic population of conformations 33 or to preferentially adopt an extended conformation 47.…”
Section: Resultsmentioning
confidence: 99%
“…The consensus K-turn sequence motif has the intrinsic capacity to adopt the familiar K-turn fold, but this conformation appears to be stabilized by intra- or inter-molecular interactions involving the flanking RNA helices distal to the kink or interactions with proteins that bind K-turns 23. Indeed, FRET measurements have shown that the K-turn motif by itself can be dynamic and converts between linear and bent conformations and that these conformational states appear to be equally populated 33, 34.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The T(GAAA)-R(11 nt) interaction also directs the bending of a kink turn in the Azoarcus group I intron (Antonioli et al 2010). Mutations of a GAAA tetraloop implicated in a tetraloop-receptor interaction in a group II intron suggested a slight morphological loop tolerance for this interaction.…”
Section: Contribution Of Gaaa Tetraloop-11 Nt Receptor Interaction Tomentioning
confidence: 99%
“…it has plasticity to some extent. 27,28 Recently, the applications of fluorescence resonance energy transfer (FRET) 29,30 have shed light on the conformation of K-turn RNAs. Many observations show that the unbound K-turn RNA exists in an extended conformation, and the metal ions could induce it to fold with its chaperon protein (L7Ae homolog proteins).…”
Section: Introductionmentioning
confidence: 99%